(untitled) (REMUNOM, 2024)
Chikungunya fever is an arbovirus caused by the Chikungunya virus, transmitted through the bite of infected female mosquitoes Aedes aegypti and Aedes albopictus. Viremia can persist for up to 10 days after the onset of clinical manifestations, which are similar to those of dengue fever, such as acute onset of fever, joint and muscle pain, nausea, headache, fatigue and rash (skin irritation). It has become an important public health problem in countries where epidemics occur, as half of the cases develop chronic, persistent and disabling arthritis. In this context, many patients end up needing physiotherapeutic follow-up in order to improve their pain and quality of life. The objective of this study was to review in the literature what is most current in the rehabilitation of these patients, through randomized clinical trials. The physiotherapeutic approach is widely indicated for patients with chronic degenerative joint diseases, especially in the subacute and chronic phases. There is evidence that resistance exercises, the Pilates method and invasive neuromodulation are not effective in the rehabilitation of individuals affected by Chikungunya fever, anxiety, pain, function efficiency and, in general, efficiency in the quality of life of these individuals.